2013
DOI: 10.1177/1077546312470473
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution for a class of fractional convection–diffusion equations using the flatlet oblique multiwavelets

Abstract: This paper is concerned with the construction of biorthogonal multiwavelet basis in the unit interval to form a biorthogonal flatlet multiwavelet system. Next a method to calculate integer and fractional derivatives of the dual flatlet multiwavelets by multiplying some matrices is suggested. The system is then used to solve a fractional convection–diffusion equation. The biorthogonality and high vanishing moments properties of this system result in efficient and accurate solutions. Finally, numerical results f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 53 publications
(47 reference statements)
0
23
0
Order By: Relevance
“…In the aforementioned results, we get approximate solution of the problem that is very close to the exact solution. To make a comparison, in Table I, we bring results of applying biorthogonal flatlet multiwavelets scheme [41] for numerical solution of the problem with D 0.5 by taking different values of m and J in time t D 0.25.…”
Section: Numerical Illustrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the aforementioned results, we get approximate solution of the problem that is very close to the exact solution. To make a comparison, in Table I, we bring results of applying biorthogonal flatlet multiwavelets scheme [41] for numerical solution of the problem with D 0.5 by taking different values of m and J in time t D 0.25.…”
Section: Numerical Illustrationsmentioning
confidence: 99%
“…A truncated Legendre series together with the Legendre operational matrix of fractional derivatives are used for numerical integration of fractional differential equations is introduced in [40]. A numerical scheme for solving the fractional convection-diffusion equation presented in [41] that is applied biorthogonal multiwavelet basis to construct operational matrix of fractional derivative. The main advantage of spectral methods lies in their accuracy for given number of unknowns.…”
mentioning
confidence: 99%
“…FCDEs can express physical problems more accurately as compared to ordinary CDEs. In this regard, the numerical and analytical solutions for FCDEs are the focus point for the researchers, and therefore different techniques have been established such as adomian decomposition method [27], Sumudu transform method and homotopy analysis transform method were used by Singh et al [28]; HPM was applied by Yildrim and Momani [29]; variational iteration technique was used by Merdan [30]; and Irandoust-pakchin et al successfully implemented the flatlet oblique multiwavelet and found a mathematical approach for the class of FCDEs [31].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, existence, uniqueness, and numerical solutions of fractional differential equations have been investigated because of application of these equations in mathematical modeling of systems and processes in the field of physics, chemistry, engineering, and so on. There are many papers that discuss about existence, uniqueness, and numerical solutions of fractional differential equations with classic boundary conditions, for example , but there exist a few papers about fractional differential equations with integral boundary conditions. Now, we introduce some of these research works.…”
Section: Introductionmentioning
confidence: 99%